2018
DOI: 10.18203/2320-6012.ijrms20182817
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow aspiration in haematological disorders: study at a tertiary care centre

Abstract: Background: The bone marrow examination is an essential investigation for the diagnosis and management of many disorders of the blood and bone marrow. Bone marrow aspiration (BMA) alone is usually sufficient to diagnose nutritional anaemias, and most of the acute leukaemias. Aim was to study the spectrum of haematological disorders diagnosed on bone marrow aspiration.Methods: This study was conducted in the Department of Clinical Haematology in Sher e Kashmir Institute of Medical Sciences, Kashmir for a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
6
9
0
Order By: Relevance
“…The high predominance of MA could be traced to the standard of living of the patients with most of them having to overcook their food most especially vegetables containing folates. This is in agreement done in India by Khan et al [17]. Iron deficiency anemia accounts for 5.2% in our study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The high predominance of MA could be traced to the standard of living of the patients with most of them having to overcook their food most especially vegetables containing folates. This is in agreement done in India by Khan et al [17]. Iron deficiency anemia accounts for 5.2% in our study.…”
Section: Discussionsupporting
confidence: 94%
“…A larger number of our patients were male with a male-female ratio of 1:0.7. This is similar to study done by Dachi et al, with a larger percentage of patients known to be male [16], reports in India by Khan et al, also shows dominance of male which is in correlation with our study [17]. Majority of the BMA were done on in-patient basis which is similar to study done by Adewoyin et al in Benin City showing that most of the patient's symptoms and management required hospitalization [18].…”
Section: Discussionsupporting
confidence: 92%
“…The lowest percentage (only one case) of myeloid dysplasia syndrome and Essential thrombocythemia was diagnosed in similar reported by the study done by Shah et al (8,16,17) .…”
Section: Discussionsupporting
confidence: 77%
“…7 preponderance similar to our findings. 8,9 However, Elmadhoun et al their study in Sudan found no difference in sex. 10 In contrast, Beddu-Addo et al in Ghana reported a female preponderance.…”
Section: Discussionmentioning
confidence: 91%
“…This is similar to what was obtained in various studies done within and outside Nigeria. [6][7][8][9] Awwalu et al in Zaria Northwestern Nigeria reported an age range of 1-78 years with male preponderance. 6 Elgesie et al in a study done in Jos, Northcentral Nigeria found an age range of 3-77 years.…”
Section: Discussionmentioning
confidence: 99%